Reducing residual‐motion artifacts in iterative 3D CBCT reconstruction in image‐guided radiation therapy. Issue 10 (5th October 2021) - Peterlik, Igor; Strzelecki, Adam; Lehmann, Mathias; Messmer, Philippe; Munro, Peter; Paysan, Pascal; Plamondon, Mathieu; Seghers, Dieter
Abstract: Purpose : Recent evaluations of a 3D iterative cone‐beam computed tomography (iCBCT) reconstruction method available on Varian radiation treatment devices demonstrated that iCBCT provides superior image quality when compared to analytical Feldkamp‐Davis‐Kress (FDK) method. However, iCBCT employs statistical penalized likelihood (PL) that is known to be highly sensitive to inconsistencies due to physiological motion occurring during the acquisition. We propose a computationally inexpensive extension of iCBCT addressing this deficiency. Methods : During the iterative process, the gradients of PL are modified to avoid the generation of motion‐related artifacts. To assess the impact of this modification, we propose a motion simulation generating CBCT projections of a moving anatomy together with artifact‐free images used as ground truth. Contrast‐to‐noise ratio and power spectra of difference images are computed to quantify the impact of the motion on reconstructed CBCT volumes as well as the effect of the proposed modification. Results : Using both simulated and clinical data, it is shown that the motion of patient's abdominal wall during the acquisition results in artifacts that can be quantified as low‐frequency components in volumes reconstructed with iCBCT. Further, a quantitative evaluation demonstrates that the proposed modification of PL reduces these low‐frequency components. While preserving the advantages of PL, it effectively suppresses the propagation of motion‐related artifacts into clinically important regions, thus increasing the motion resiliency of iCBCT. Conclusions : The proposed modified iterative reconstruction method significantly improves the quality of CBCT images of anatomies suffering from residual motion.